DIGITAL CONTENT STRATEGY: HOW SOCIAL PROOF INFLUENCES PURCHASING DECISIONS - Siregar, Ade Perdana; Setiawan, Wahyu Juari (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
The growth of the creative industry in Indonesia has become a pillar in the economy, this phenomenon has illustrated that human resources have the potential to be ready for competitiveness towards foreign countries. Marketing through online media has become an idol for business actors, in addition to being very easy to use, it is supported by small promotional costs. Managing information content on social media is very important, in addition to creating attraction, it also fosters consumer trust to choose to transact to buy a product. The objectives of this study are (1) To examine the influence of smart digital content marketing on purchasing decisions; (2) To examine the influence of smart digital content marketing on social proof; (3) To examine the influence of social proof on purchasing decisions; (4) To examine the role of social proof in mediating the influence of smart digital content marketing on purchasing decisions. The data analysis method used is Structural Equation Modeling (SEM) measurement using SmartPLS software. The results of the analysis show that Smart Digital Content Marketing has a positive and significant effect on Purchasing Decisions. In addition, Social Proof also has a significant effect on Purchasing Decisions and mediates the relationship between Smart Digital Content Marketing and Purchasing Decisions. This finding confirms the importance of the presence of social proof as a reinforcement of the effectiveness of digital marketing strategies in driving consumer purchasing decisions.